PELAYANAN PRIMA PADA KANTOR KECAMATAN RAWALUMBU PEMERINTAH KOTA BEKASI - Morlian, Amanda (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2015)
Lack of awareness, lack of expertise and skills, lack of fulfillment revenue service employees, and ideally less infrastructure services are some of the things that cause obstacles and barriers. So it can be said that the excellent service in the manufacture of identity cards (KTP) has not been fully demonstrated that optimal care of excellent service is expected. Based on the research conducted, there are several factors that become obstacles in the ID card service, such as a lack of awareness of the officer factor through the willingness to carry out the task, the lack of discipline level employees, the lack of fulfillment (income), as well as the lack of adequate facilities factors. In an attempt to overcome these obstacles include a lack of awareness of employees, to provide guidance or rules of discipline, fulfilling the needs of employees, the addition of devices means that there Swamp Lumbu Bekasi city government offices. Awareness Employees who carry out tasks that one of the determinants of comfort government based on the spirit of devotion and establish a good working atmosphere with various related parties to each other and need each other in order to facilitate the task of the ministry